1995
DOI: 10.1007/bf01464473
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and subcellular distribution of glucokinase in rat liver and their changes during fasting-refeeding

Abstract: The distribution of glucokinase in rat liver under both normal feeding and fasting-refeeding conditions was investigated immunohistochemically. Under normal feeding conditions, glucokinase immunoreactivity was observed in both nuclei and cytoplasm of parenchymal cells. The nuclei were stained intensely and evenly, whereas the cytoplasm showed weak immunoreactivity of different degrees of staining intensity depending on the location of the cells. The cytoplasm of perivenous hepatocytes was stained more intensel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
7
28
0
Order By: Relevance
“…We suggest (Fig. 6) that periportal glycogen is synthesized from G6P derived from cytosolic (active) GK, which is present throughout the lobule in fully refed animals (13) and not from gluconeogenically derived G6P. Several lines of evidence support this contention.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…We suggest (Fig. 6) that periportal glycogen is synthesized from G6P derived from cytosolic (active) GK, which is present throughout the lobule in fully refed animals (13) and not from gluconeogenically derived G6P. Several lines of evidence support this contention.…”
Section: Discussionmentioning
confidence: 77%
“…(The half-lives of GK activity and GK mRNA are 30 h and 45 min respectively [30,31].) During fasting, GK is tightly bound to the inhibitory GK regulatory protein (GKRP) (32) in the nucleus (33) (except perivenously [13]). Farrelly et al (34) and Grimsby et al (35) demonstrated that knockout of the GKRP in mice resulted in decreased hepatic GK activity, suggesting that an impor- tant function of nuclear sequestration of GK during starvation might be to delay degradation of GK protein, which is relatively easily inactivated by oxidation in vitro (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver slices were dehydrated, embedded in paraffin, and sectioned at a thickness of 3 m. The sections were mounted on silanized slides. Immunohistochemical staining was carried out as described previously (16). The total optical density of GK in the nucleus was quantitated and normalized by the total area of nucleus by computerized image analysis using Image-Pro Plus software (Planetron Inc. Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Fructose 1-phosphate may also contribute to glycogen accumulation by inhibition of glycogen phosphorylase [27]. Since in livers from 48-h starved rats glucokinase activity (and enzyme protein concentration [28]) are markedly concentrated in the most perivenous cells [15], where the accumulation of fructose 1-phosphate is greatest ( Figure 5), glucokinase activation would occur primarily in those cells and present Figure 5 Fractional change in PME during fructose infusion, and the relationship to ∆ATP Top panel : fractional change in PMEs (predominantly fructose 1-phosphate) concentration during fructose infusion (compared with pre-fructose), plotted against FVR. MeanspS.E.M.…”
Section: Figure 3 Hepatic Lactate Uptake Before ($) and During (#) Thmentioning
confidence: 99%